Spread of Islam in Pre-Mughal Bengal - AI-Ahsan, Abdullah (Intellectual discourse, 1994)
Today's Muslim-majority Bangladesh is surrounded by non-Muslim northernIndia in the west and Buddhist Myanmar in the east. Many non-Muslim scholarshave argued that force was applied in converting indigenous Hindus, while anumber of Muslim scholars have emphasized the migration of Muslims from otherparts of India, as an explanation. Scholars have differences of opinionregarding the time when Bangladesh became a Muslim-majority area. This paperargues that the area constituting Bangladesh was Buddhist majority area beforeconversion to Islam, and that this conversion was largely voluntary, throughthe preaching of sufis. Bengal had already become a Muslim-majority area whenMughals arrived there.